2016
DOI: 10.1371/journal.pone.0156052
|View full text |Cite
|
Sign up to set email alerts
|

Is the Colonisation of Staphylococcus aureus in Pets Associated with Their Close Contact with Owners?

Abstract: In human beings and animals, staphylococci constitute part of the normal microbial population. Staphylococcus aureus could be classified as an opportunistic pathogen because the bacteria are noted in clinically healthy individuals, but when the immune system becomes compromised, they can also cause a wide range of infections. The objective of this study was to test the hypothesis that cats who are in close contact with their owners are at the greatest risk of being colonised with S. aureus. Two groups of cats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 72 publications
6
51
0
3
Order By: Relevance
“…On the other way round, several studies showed that MRSA in pets are mostly of human origin [28] and there is a correlation between close contact with humans and increased risk of colonization of pets with S. aureus [29]. This is also consistent with the fact that S. aureus is not a common colonizer of cats and dogs, in contrast to S. pseudintermedius.…”
Section: Mrsa In Companion Animalsmentioning
confidence: 60%
“…On the other way round, several studies showed that MRSA in pets are mostly of human origin [28] and there is a correlation between close contact with humans and increased risk of colonization of pets with S. aureus [29]. This is also consistent with the fact that S. aureus is not a common colonizer of cats and dogs, in contrast to S. pseudintermedius.…”
Section: Mrsa In Companion Animalsmentioning
confidence: 60%
“…The prevalence of S. aureus carriage reported in dogs and cats varies considerably between study populations and methodologies (Abraham, Morris, Griffeth, Shofer, & Rankin, ; Boost et al, ; Fazakerley et al, ; Griffeth, Morris, Abraham, Shofer, & Rankin, ). The degree of human contact has been shown to influence the prevalence of S. aureus carriage in cats and dogs, with prevalence of carriage much lower in stray and wild populations than in pets (Bierowiec, Ploneczka‐Janeczko, & Rypula, ; Boost et al, ). Information was not collected in this study about interactions between pets and their owners.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ST6 SCC mec type IV (t304) pvl- negative MRSA, a strain susceptible to non-beta-lactams, was previously isolated from patients overseas, suggesting that the ST6 strain isolated in our study may be capable of causing human infection [ 23 ]. In addition, CC6-ST6-t304 strains have previously been isolated from human (MSSA and MRSA), feral cat (MRSA) and camel (MSSA) suggesting that the strain may be transmissible across different host species [ 19 , 24 26 ].…”
mentioning
confidence: 99%